1986
DOI: 10.1002/anie.198604801
|View full text |Cite
|
Sign up to set email alerts
|

ESR Observation of Thermally Produced Triplet Nitrenes and Photochemically Produced Triplet Cycloheptatrienylidenes

Abstract: The fascinating carbene‐nitrene rearrangement can be observed directly by ESR spectroscopy. In the thermal decomposition of the carbene precursor 4 (via 3) with subsequent matrix isolation, the product gave the same ESR signal as phenylnitrene 2 from phenylazide 1! In the aza‐analogous system, the seven‐membered carbene 5 is probably formed as intermediate of the rearrangemet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
0
5

Year Published

1992
1992
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(121 citation statements)
references
References 15 publications
7
109
0
5
Order By: Relevance
“…There is a reversal of energy ordering at the G2(RMP2,SVP)//QCI (E e ) level, 54 with 3 A 2 preferred by 2 kJ mol -1 . This result is in agreement with recent CASPT2N calculations of Schreiner et al 40 The prediction of a stable triplet state of 3 is in agreement with the observation of cycloheptatrienylidene by ESR spectroscopy, 21 although current calculations do not permit a clear conclusion as to which state is being observed. Since the singlet 1 A 2 state is calculated to lie lower in energy than the closely related 3 A 2 state, 39,40 the 3 A 2 carbene may be expected to easily (53) Schlegel, H. B. J. Chem.…”
Section: Discussionsupporting
confidence: 93%
“…There is a reversal of energy ordering at the G2(RMP2,SVP)//QCI (E e ) level, 54 with 3 A 2 preferred by 2 kJ mol -1 . This result is in agreement with recent CASPT2N calculations of Schreiner et al 40 The prediction of a stable triplet state of 3 is in agreement with the observation of cycloheptatrienylidene by ESR spectroscopy, 21 although current calculations do not permit a clear conclusion as to which state is being observed. Since the singlet 1 A 2 state is calculated to lie lower in energy than the closely related 3 A 2 state, 39,40 the 3 A 2 carbene may be expected to easily (53) Schlegel, H. B. J. Chem.…”
Section: Discussionsupporting
confidence: 93%
“…[180] Mehrere andere,schwingungsmäßig kalte freie Radikale wurden durch Pulspyrolyse erhalten, [181] einschließlich des Methylradikals. [184,185] Cyclopropenyliden (94), Propadienyliden (95)u nd Propargylen (96) wurden durch Pulspyrolyse von 3-Chlorcyclopropen, 1,3-Dibrompropin bzw.3-Diazopropin erhalten [Gleichungen (46)- (48)] und durch ihre Massen-und Photoelektronenspektren charakterisiert. [183] Alkylradikale,d ie durch gepulste Pyrolyse entstanden waren, sind durch Photoionisierung mit Femtosekundenauflçsunganalysiert worden.…”
Section: Gepulste Pyrolyse (Strahlexpansions-fvp)unclassified
“…(23)]. [96] Analog wurden die EPR-Spektren vieler anderer Aryl-und Heteroarylnitrene beobachtet (Naphthyl-, Phenanthryl-, Pyridyl-, Pyrimidinyl-, Pyrazinyl-, 3-Pyridazinylnitrene und so weiter). [58] Die gleiche Methode bei ähnlicher Apparatur wurde auch eingesetzt, um das IR-Spektrum von Phenylnitren in Ar-Matrix zu erhalten.…”
Section: Epr- Ir-und Uv/vis-spektroskopieunclassified
See 1 more Smart Citation
“…Carbene T-4 could be independently synthesized and characterized by matrix EPR spectroscopy. [8] According to calculations at the CCSD(T) level of theory, allene 2 is about 13 kcal/mol more stable than carbene T-1, and carbene T-4 lies more than 25 kcal/mol above 2. [9] In this study, the earlier assignment of the IR spectra of 1 and 2 was confirmed.…”
Section: Introductionmentioning
confidence: 99%